Persistent Incisional Pain after Noncardiac Surgery: An International Prospective Cohort Study. (9th September 2021) - Khan, James S.; Sessler, Daniel I.; Chan, Matthew T. V.; Wang, C. Y.; Garutti, Ignacio; Szczeklik, Wojciech; Turan, Alparslan; Busse, Jason W.; Buckley, D. Norman; Paul, James; McGillion, Michael; Fernández-Riveira, Carmen; et al.
Abstract : Background: The purpose of this study was to determine the incidence, characteristics, impact, and risk factors associated with persistent incisional pain. The hypothesis was that patient demographics and perioperative interventions are associated with persistent pain. Methods: This was a secondary analysis of an international prospective cohort study from 2012 to 2014. This study included patients who were 45 yr of age or older who underwent major inpatient noncardiac surgery. Data were collected perioperatively and at 1 yr after surgery to assess for the development of persistent incisional pain (pain present around incision at 1 yr after surgery). Results: Among 14, 831 patients, 495 (3.3%; 95% CI, 3.1 to 3.6) reported persistent incisional pain at 1 yr, with an average pain intensity of 3.6 ± 2.5 (0 to 10 numeric rating scale), with 35% and 14% reporting moderate and severe pain intensities, respectively. More than half of patients with persistent pain reported needing analgesic medications, and 85% reported interference with daily activities (denominator = 495 in the above proportions). Risk factors for persistent pain included female sex ( P = 0.007), Asian ethnicity ( P < 0.001), surgery for fracture ( P < 0.001), history of chronic pain ( P < 0.001), coronary artery disease ( P < 0.001), history of tobacco use ( P = 0.048), postoperative patient-controlled analgesia ( P < 0.001), postoperative continuous nerve block ( P = 0.010), insulin initiation within 24 h of surgery ( P < 0.001), and withholding nonsteroidal anti-inflammatory medication or cyclooxygenase-2 inhibitors on the day of surgery ( P = 0.029 and P < 0.001, respectively). Older age ( P < 0.001), endoscopic surgery ( P = 0.005), and South Asian ( P < 0.001), Native American/Australian ( P = 0.004), and Latin/Hispanic ethnicities ( P < 0.001) were associated with a lower risk of persistent pain. Conclusions: Persistent incisional pain is a common complication of inpatient noncardiac surgery, occurring in approximately 1 in 30 adults. It results in significant morbidity, interferes with daily living, and is associated with persistent analgesic consumption. Certain demographics, ethnicities, and perioperative practices are associated with increased risk of persistent pain. Abstract : Incisional pain persisting for up to 1 yr after major noncardiac surgery was assessed prospectively in a cohort of more than 14, 000 patients. Persistent incisional pain was identified in 3.3% of the patients, with nearly half reporting moderate to severe pain. Several risk factors, including female sex, history of chronic pain, coronary heart disease, and others, were identified.